Talent Management and Employee Engagement - Aljunaibi, Mohamed Musallam (2014)
In the last decade, Talent Management and Employee Engagement, and their impact on organizational performance have been widely studied in academic literature. As most of those studies were conducted in western contexts, this study aims to provide a comprehensive understanding of relationship of talent management and employee engagement and investigate the impact of talent management practices on employee engagement in semi-government organizations in Abu Dhabi, UAE. To achieve the objectives of this research a literature review was conducted to provide a better understanding of the two concepts and to identify the main talent management factors that impact employee engagement. Moreover, to provide empirical evidences of the relationship of the concepts, a quantitative study was done by distributing a survey to employees working in the oil and gas industry. The Survey was divided into three main sections; demographic, Talent Management and Employee Engagement section. This structure aimed to have optimal understanding of the background of the respondents and to measure the elements that are relevance to the concepts targeted in this study. The findings indicate that talent management factors such as talent development, recognition, and leadership support have a positive correlation with employee engagement. Thus, this study recommends that organizations interested in increasing levels of employee engagement need to establish proper talent management systems that focus on talent development, support from management, and simultaneously look into enhancing policies and working environments. Finally, the research provides some suggestions for future researchers to improve the understanding and impact of talent management practices on employee engagement.